1988
DOI: 10.1111/j.1365-2044.1988.tb08987.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced brachial plexus blockade. Effect of pain and muscular exercises on the efficiency of brachial plexus blockade

Abstract: One or the disadvantages of brachial plexus block is thc latency of onset. which may be as long as 30 m i n~t e s .~ It has been postulatcd that high frcqucncy nerve impulses increase anaesthetic effectivene~s,~ and hence this study was designed to invcstigatc the effect of pain and muscle excrcise in enhancing the onset of analgcsia and motor block aftcr brachial plexus blockade. MPlhild.7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…242 Because local anesthetic blockade of sodium channels is usedependent, exercising the arm after block placement significantly speeds up anesthesia onset but does not improve success or prolong duration. 243 Conversely, the use of transcutaneous nerve stimulation to Bexercise the arm[ is of no benefit. 244 Rapid injection of local anesthetic reduces anesthetic spread and increases failure rate.…”
Section: Physical Manipulationsmentioning
confidence: 99%
“…242 Because local anesthetic blockade of sodium channels is usedependent, exercising the arm after block placement significantly speeds up anesthesia onset but does not improve success or prolong duration. 243 Conversely, the use of transcutaneous nerve stimulation to Bexercise the arm[ is of no benefit. 244 Rapid injection of local anesthetic reduces anesthetic spread and increases failure rate.…”
Section: Physical Manipulationsmentioning
confidence: 99%
“…9 Yet, correct pathogen identification is paramount for timely management, successful antibiotic stewardship, and for minimizing the growing risk of antibiotic-resistant organisms, which is an increasingly concerning barrier to care in the United States. While the incidence of causative organisms for pediatric OM varies by region, Staphylococcus aureus is often reported as the most common pathogen 10,11 ; a recent case study of cutaneous methicillin-resistant S aureus infections demonstrated a resistance to clindamycin in 13% of cases, highlighting the rapid growth of multi-drug resistant organisms. 12 As such, in patients who otherwise may not require surgery, interventional radiology (IR)-guided biopsy may allow for timely, sensitive, and accurate pathogen identification.…”
mentioning
confidence: 99%